Increase in financial availability in Vietnam on the basis of the principles of retail payment services development - Chan Shon Tung (Путеводитель предпринимателя, 2020)
The author on the basis of the principles of development of retail payment services developed by him for the problem resolution offinancial availability, reveals problems ofavailability of retailpayment services in Vietnam and proposes measures for their decision.